Does the fintech ecosystem promote effective financial inclusion in Kenya? - Odongo Kodongo (Kenya Bankers Association (KBA), 2023)
We examine the effect of the fintech ecosystem on the consumption of formal financial services such as savings, credit and use of capital markets instruments in Kenya. We deploy Probit regression on data from FinAccess Survey for 2016 and 2021. Findings suggest that the fintech ecosystem facilitates credit evaluation and fosters credit use, offer financial products and services that better match users' needs hence fostering usage of those services, but does not mitigate the distance barrier. Second, the probability of an individual enjoying fintech ecosystem services falls by at least 19% if the individual resides in Northern Kenya. Third, the fintech ecosystem increases the probability of usage of traditional services of financial institutions by at least 5.2%. Fourth, the financial inclusion gains of the fintech ecosystem are not uniform across all user categories. We recommend several policy actions such as improved provisioning of physical infrastructure in remote areas, fiscal policy incentives, and affirmative action on financial inclusion.
Keywords: 330